PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN DANA PERIMBANGAN TERHADAP KEMANDIRIAN KEUANGAN PEMERINTAH DAERAH - Rahmat Saleh (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
Local Financial Independence has become one of the main factors to determine whether a local government has optimizing their Local Original Revenue earnings or still depend on their Transfer Revenue, particularly Fiscal Funds from state government, to implement their governance. The purposes of this research are to study the effect that the Local Original Revenue has against Local Financial Independence, to study the effect that the Fiscal Funds has against Local Financial Independence, and to study the effect that both Local Original Revenue and Fiscal Funds have against Local Financial Independence. The data analyzing, methods such as Multiple Linear Regression, F-test and t-test were used to study the effect both independent variables have against the dependent variable. The findings of the study indicate that Local Original Revenue had a positive effect against Local Financial Independence, Fiscal Funds had a negative effect against Local Financial Independence, and Local Original Revenue and Fiscal Funds simultaneously had effect against Local Financial Independence.